2019
DOI: 10.1021/acs.biochem.9b00655
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Soluble Species of β-Amyloid and α-Synuclein Promote Oligomerization while Inhibiting Fibrillization

Abstract: Aggregations of β-amyloid (Aβ) and α-synuclein (αS) into oligomeric and fibrillar assemblies are the pathological hallmarks of Alzheimer's and Parkinson's diseases, respectively. Although Aβ and αS affect different regions of the brain and are separated at the cellular level, there is evidence of their eventual interaction in the pathology of both disorders. Characterization of interactions of Aβ and αS at various stages of their aggregation pathways could reveal mechanisms and therapeutic targets for the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 88 publications
3
19
0
Order By: Relevance
“…While structural information for the Aβ oligomers induced by αS has still not been reported, further investigation could provide more details to establish a correlation between AD and PD. 297 The aggregation and folding of αS is shown to be modulated by the isomeric state of the five proline residues (P108, P117, P120, P128, and P138) located in the disordered C-terminus. 298 Among the five-proline residues, isomerization of P128 is identified to be catalyzed by cyclophilin A (CypA), a protein belonging to the family of peptidylprolyl isomerases.…”
Section: α-Synuclein and Tau Proteinsmentioning
confidence: 99%
“…While structural information for the Aβ oligomers induced by αS has still not been reported, further investigation could provide more details to establish a correlation between AD and PD. 297 The aggregation and folding of αS is shown to be modulated by the isomeric state of the five proline residues (P108, P117, P120, P128, and P138) located in the disordered C-terminus. 298 Among the five-proline residues, isomerization of P128 is identified to be catalyzed by cyclophilin A (CypA), a protein belonging to the family of peptidylprolyl isomerases.…”
Section: α-Synuclein and Tau Proteinsmentioning
confidence: 99%
“…As αSyn was initially described as the non-amyloid component of amyloid plaques (NACP) [77], the direct interactions and copolymerization of αSyn and Aβ have been reported in many in vitro studies [67,[78][79][80][81][82][83]. In fact, PFFs have been shown to be able to nucleate Aβ aggregation [84]; however the literature on this topic is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PFFs have been shown to be able to nucleate Aβ aggregation [84]; however the literature on this topic is complicated. In 2020, Candreva et al, demonstrated that αSyn monomers and oligomers co-assemble with Aβ, stabilizing Aβ oligomers and thus preventing Aβ fibrillization, whereas αSyn fibrils did not change fibrillization [83]. Furthermore, the effect of αSyn on Aβ fibrilization was lost when aggregation studies were seeded with preformed Aβ fibrils [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been found that α-syn can either accelerate or inhibit the aggregation of Aβ. This dual mechanism of α-syn has been observed on both the 40-residue-long (Aβ40) and the 42-residue-long (Aβ42) isoforms of Aβ (22,(34)(35)(36)(37)(38). Whether α-syn promotes or inhibits Aβ aggregation seems to depend on the aggregated state of α-syn.…”
Section: Introductionmentioning
confidence: 95%